2017
DOI: 10.1016/j.ccell.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Checkpoint Decisions Made by Subverted Vascular Niche Transform Indolent Tumor Cells into Chemoresistant Cancer Stem Cells

Abstract: Summary Tumor-associated endothelial cells (TECs) regulate tumor cell aggressiveness. However, the “core” mechanism by which TECs confer stem cell-like activity to indolent tumors is unknown. Here, we used in vivo murine and human tumor models to identify tumor-suppressive checkpoint role of TEC-expressed insulin growth factor (IGF) binding protein-7 (IGFBP7/angiomodulin). During tumorigenesis, IGFBP7 blocks IGF1 and inhibits expansion and engraftment of tumor stem-like cells (TSCs) expressing IGF1-receptor (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 53 publications
1
78
2
Order By: Relevance
“…Hence, IGFBP7 could represent a common target of different signalling pathways to sustain stem cell features. In this respect, a role of IGFBP7 as inhibitor of the expansion and aggressiveness of tumour stem-like cells was recently proved in vivo (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, IGFBP7 could represent a common target of different signalling pathways to sustain stem cell features. In this respect, a role of IGFBP7 as inhibitor of the expansion and aggressiveness of tumour stem-like cells was recently proved in vivo (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R activation has been implicated in resistance to both chemical and radiation based therapies. Investigations in several different tumour types have revealed increased IGF activity in chemoresistant tumours and shown that IGF1R inhibition acts as a chemosensitizer (Dallas et al ., ; Eckstein et al ., ; Juan et al ., ; Ireland et al ., ; Cao et al ., ). Downstream activation of the PI3K/AKT pathway has been shown to be instrumental to the mechanism of chemoresistance in many of these studies.…”
Section: Role Of Igf System In Chemoresistancementioning
confidence: 97%
“…(42) Cao et al described that TEC convert indolent tumor cells to more aggressive cells with greater tumorigenicity, extranodal invasion, and chemoresistance. (42,43) Moreover, other groups have also demonstrated that the Notch signals in EC are involved in tumor progression and stem cell phenotype. (44)(45)(46)(47) Notch activation in EC promotes tumor cell migration and metastasis along with neutrophil infiltration.…”
Section: Role Of Tumor Endothelial Cells In Tumor Progression and Metmentioning
confidence: 99%